"Don't smile until December": Bad advice based on the either-or fallacy. Issue 4 (2nd October 2022) - Vomund, Jeff; Miller, Angela D.
ABSTRACT: Despite over 30 years of educational research to the contrary, some educators continue to hold to classroom management theories along the lines of "don't smile until December, " which pits consistency and control in the classroom against the kindness and caring that should also characterize the learning environment. We address the source of this controversy as faulty reasoning that sees expressions of care as competing with instructional values such as rigorous lessons from teachers and high expectations for students. In fact, research suggests that from student perspectives, quality teaching and high expectations do not compete with caring but express it. We suggest 3 teaching strategies that illustrate how these seemingly disparate aspects of teaching are connected. Further, we consider how teachers can use cognitive empathy to carry out these strategies effectively. The article closes with examples of how these strategies can be practically implemented in classrooms.